Method for producing silicon-based electrode materials

Coating silicon particles with carbon to stabilize the SEI layer on lithium-ion batteries addresses the degradation issues of silicon electrodes, enhancing energy efficiency and cycle stability by preventing lithium consumption and maintaining conductivity.

JP7624458B2Active Publication Date: 2025-01-30FRAUNHOFER GESELLSCHAFT ZUR FORDERUNG DER ANGEWANDTEN FORSCHUNG EV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022574638
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-03
Filing Date
2021-06-02
Publication Date
2025-01-30
Estimated Expiration
2041-06-02

AI Technical Summary

Technical Problem

Existing lithium-ion batteries using silicon as a negative electrode face significant challenges due to the chemical and mechanical degradation of silicon particles during lithium ion incorporation, leading to reduced storage capacity and increased internal resistance, as the formation of an inconvenient solid electrolyte interface (SEI) layer consumes lithium and hinders charge carrier transport.

Method used

The method involves coating silicon particles with carbon before use in batteries to form a stable SEI layer only on the carbon surface, preventing direct chemical reaction with the electrolyte and maintaining conductivity between particles, thereby stabilizing the battery over multiple cycles.

Benefits of technology

This approach enhances the energy efficiency and cycle stability of lithium-ion batteries by reducing the consumption of lithium for SEI formation and maintaining charge carrier transport, resulting in improved energy density and extended battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624458000014
    Figure 0007624458000014
  • Figure 0007624458000015
    Figure 0007624458000015
  • Figure 0007624458000016
    Figure 0007624458000016
Patent Text Reader

Abstract

The subject of the present invention is a method for producing a silicon-carbon composite material. This composite material can be used as an active material for the negative electrode of a silicon-based lithium-ion battery, or can be further processed to form such an active material. When used as a lithium reservoir, the composite material is characterized by a particularly high specific capacity and a particularly long charge-discharge cycle-dependent life.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The subject of the present invention is a silicon-carbon composite (Si / C composite) and a method for producing the silicon-carbon composite, which can be used as an active material for the negative electrode of a silicon-based lithium-ion battery, or which can be further processed to form such an active material. [Background technology]

[0002] When used as lithium stores, the composite materials are characterized by a particularly high specific capacity and a long charge-discharge cycle-dependent lifetime for such materials.

[0003] The proposed method allows the production of cost-efficient active materials for the storage of lithium ions in lithium ion batteries on an industrial scale. This material can be used as a "Drop-In-Replacement" of materials used according to the current prior art, in particular graphite, in existing manufacturing plants for lithium ion batteries. The aforementioned material can consequently reduce the manufacturing costs of lithium ion batteries and at the same time increase both the volumetric and gravimetric energy density of the battery, thus benefiting all known applications in which electrical energy storage is used, in particular in the case of mobile applications such as electromobility and all types of portable electronic devices.

[0004] The object of the present invention is to make a significant contribution to reducing the cost of lithium-ion batteries by providing a new material for the negative electrode of a lithium-ion battery cell and by a new method for its manufacture, while at the same time increasing the energy stored in the battery for each unit of weight or volume. Silicon is in principle very suitable as a material for the negative electrode, but during the operation of the battery cell, silicon undergoes chemical and mechanical changes, so that its availability to take up lithium during repeated charging and discharging of the battery cell is reduced.

[0005] Traditionally, lithium ions are incorporated into graphite during charging of lithium-ion batteries. In this way, up to 372 mAh of charge can be stored in the battery per gram of graphite. In the search for new materials that allow to increase the energy density of batteries, the attention of battery manufacturers in recent years has focused on silicon as a suitable alternative to graphite. Silicon has the potential to incorporate more than ten times the amount of lithium ions in proportion to its mass. In this case, the theoretical limit of the specific capacity of the active material is about 4200 mAh per gram of silicon. In practice it has been possible to achieve this value approximately, but after only a few cycles the usable capacity drops significantly. The reason for this is that when lithium ions are incorporated into the silicon structure, the volume of the silicon-lithium alloy expands very significantly (Zhang L et al:Si-containing precursors for Si-based anode materials of Li-ion batteries:A review,in:Energy Storage Materials 4(2016)S.92-102). This process leads to further mechanical destruction of the silicon particles. By developing aluminum-based metallurgical silicon alloys, it has indeed been possible to significantly improve these properties of the material, but the degradation of the material is still relatively significant.

[0006] From US Pat. No. 5,399,533, inter alia, a method is known in which silicon particles are coated with carbon by pyrolysis of saccharose. The material produced in this way should be suitable for use as active material in lithium-ion batteries. In this case, carbon particles are mixed into the starting mixture. In addition, a carboxylic acid must be added. A very high proportion of graphite particles is used in the method described therein, and the coating method is carried out in a single step. The resulting composite material achieves a discharge capacity of less than 500 mAh / g.

[0007] Non-Patent Document 1 addresses the problem of the fracture of silicon microparticles as a result of lithium absorption. To solve this problem, it is proposed to surround the silicon microparticles with a graphene cage that has a cavity to allow the expansion of the microparticles. In this case, the fracture of the microparticles is not prevented, but rather the fragments are held within the cage.

[0008] One of the criteria that determines the functioning of lithium-ion batteries is the formation of a suitable passivation layer on the surface of the negative active material. The use of silicon as a host for storing lithium ions without further measures leads to the formation of undesirable layers, especially of lithium silicate, on its surface. As a result of the destruction of silicon, especially due to the volume expansion when lithium is incorporated, new Si surfaces are continuously formed, which in turn allows the formation of new undesirable layers on the new Si surfaces during subsequent charging cycles. The formation of these layers during each charging process consumes lithium, which is then no longer actively available for charge carrier transport, thus consuming energy. The number of charge carriers available in the battery is reduced, and the transport of lithium ions into the silicon particles is hindered. Thus, the battery loses its storage capacity with each cycle and may become unusable for its intended purpose. This must be prevented during the intended life (expected number of cycles) of the battery, which must always be used at its minimum charge capacity. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] US Patent Application Publication No. 2015 / 0295233 [Non-patent literature]

[0010] [Non-Patent Document 1] Li Y et al.: Growth of conformal graphene cages on micrometer-sized silicon particles as stable battery anodes, in Nature Energy 1,15029(2016) Summary of the Invention [Problem to be solved by the invention]

[0011] The method according to the invention provides for preventing, as far as possible, the progression of the aforementioned undesirable formation of a passivation layer, and therefore also the progression of the removal of lithium necessary for charge carrier transport, due to the fact that the silicon particles are covered and thus protected with a suitable coating of carbon before being used in the battery.

[0012] If this carbon coating is properly selected, a direct chemical reaction between the electrolyte and silicon can be avoided. Instead, a layer known as the SEI (solid electrolyte interface) layer is formed only on the surface of the carbon coating that is in direct contact with the electrolyte. The boundary layer is therefore very limited in terms of its extent (initial growth), in a manner similar to the prior art of graphite-based anode materials, and from then on, stable conditions can be achieved in terms of charge carrier transport through these layers without further continuous increase in the internal resistance of the battery with increasing number of cycles. A relatively stable state arises after only a few cycles, in which case the electrolyte is not further decomposed and no significant amount of lithium is continuously consumed due to the formation of a growing passive layer, which is then no longer available to the battery as a storage capacity. In contrast to the SEI layer of silicon particles not covered with carbon, favorable conditions can be achieved by a suitable coating for battery cycle stability. As a result of this, a passive layer is generated on the surface of the carbon coating, ideally in a single shot, which has a favorable effect on the long life of the battery. Such stabilized SEI layers are known from the prior art for graphite anodes and consist mainly of lithium carbonate, lithium methyl carbonate and lithium ethylene dicarbonate (Decomposition Reactions of Anode Solid Electrolyte Interphase (SEI) Components with LiPF6, J. Phys Chem. C2017, 121, pp22733-22738).

[0013] The stabilization of these SEI boundary layers between the carbon and the electrolyte is performed by the selection of suitable electrolyte additives, which are known from the prior art.

[0014] At the same time, the carbon coating of the silicon particles ensures that the electrical conductivity between the individual composite particles of the aforementioned material is permanently maintained and is not continuously diminished by the ongoing SEI growth, which results in an improved energy efficiency of the batteries produced therefrom. It may even give rise to the possibility of omitting conductive additives in the battery electrodes, which would result in a further increase in the overall energy density of the battery. In particular, the carbon layer, at least partially composed of structured carbon such as graphene or graphene-type compounds, is permeable to lithium ions, thus allowing the operation of the battery cell while the silicon is protected from chemical attack.

[0015] It is therefore an object of the present invention to provide an improved material for the anode of lithium-ion batteries, which makes it possible to obtain more efficient batteries with a longer service life. A further object is to provide a simple and particularly low-cost method for producing silicon-carbon composite materials for battery applications. This object is achieved by the subject matter of the present invention. [Means for solving the problem]

[0016] One of the important criteria for the functioning of a lithium-ion battery cell is the formation of a suitable passivation layer on the surface of the active material of the negative electrode, known as the "SEI" (solid electrolyte interphase interface). If, without further measures, silicon is used in the aforementioned respects as a host for storing Li-ions, layers unfavorable to the functioning of the battery cell, including lithium silicate and other reaction products, will form on its surface in interaction with the electrolyte. As a result of the significant expansion of the volume when lithium is incorporated into silicon, silicon particles are destroyed or cracks are formed in them, so the further formation of these unfavorable layers leads to an ever-increasing consumption of silicon and lithium for the growth of these undesirable layers with each charging process. The number of charge carriers and the proportion of active material available in the battery cell are reduced as a result of this. Moreover, the transport of lithium ions to the silicon particles and back to the cathode side is hindered by the growing unfavorable layers, and furthermore, the electronic conductivity between the particles is considerably reduced. As a result, the battery forms an increasingly high internal resistance.

[0017] The method according to the invention particularly largely prevents the formation of this unfavourable passive layer on the silicon surface, due to the fact that the silicon particles are covered and thus protected with a suitable layer of carbon before their use in the battery electrodes. As a result of this, a passive layer, which has a favourable effect on the cycle durability or the maintenance of the capacity of the battery cell over a large number of cycles, is generated on the surface of the carbon, ideally only once during the first charge, similar to the use of graphite instead of silicon. The carbon coating further results in that the electrical conductivity between the individual particles of said material is maintained over an increased life of the battery, and the charge carrier transport between the battery electrodes remains fully guaranteed over a significantly greater number of charge and discharge cycles. As a result of this, the energy efficiency of the battery cell made from this composite of silicon particles covered with carbon is significantly improved compared to a battery cell made only from silicon particles. As a result, the battery cell can also be charged significantly more quickly. In particular, the carbon layer (coating), which may be at least partially composed of structured carbon, such as graphene or graphene-type structures, and which may have a scale-like arrangement on the silicon surface, is permeable to lithium ions, thus allowing the operation of the battery cell while the silicon is protected from chemical attack. As a result, a composite material can be produced having one or more silicon particles embedded in a matrix made from the described carbon material.

[0018] The specific size of the active surface is further relevant to the usefulness of this composite material in a battery cell, since it also determines the amount of the passive layer produced and is therefore also an important factor in the coulombic efficiency of the battery. The term active surface in this context means the surface of the composite particle that interacts with the electrolyte of the battery cell. This size can be determined, for example, by BET measurements (adsorption / desorption characteristics). In the present method according to the invention, the specific size of the active surface can be influenced through the control of the process parameters. The person skilled in the art understands the term specific surface area of ​​an object as the quotient of the surface of the object and its mass. As a result, it is possible to produce composite particles that have a specific active surface area that is lower than the specific surface area of ​​the silicon particles contained in the interior of the composite particle in the initial state. As a result, silicon particles that are small enough that they no longer break during lithium absorption can also be used, without the specific surface area (BET measurement) of the small particles inside the composite adversely affecting the coulombic efficiency of the battery cell. In one embodiment, the composite material has a specific surface area that is not more than twice as large, in particular less than 50% as large, than the specific surface area of ​​the silicon particles in the composite material.

[0019] One preferred feature of the present invention is that the active Si surface of the composite particles that is exchanged with the electrolyte in the battery cell is reduced by at least a factor of 10 compared to when no carbon coating is applied around the silicon particles.

[0020] The silicon particles used are preferably approximately spherical.In particular, the ratio of the maximum diameter to the minimum diameter of the particle is at most 1.5:1, preferably at most 1.3:1, particularly preferably at most 1.2:1 or at most 1.1:1.This applies in particular to the majority of the particles, i.e. more than half of the particles, or even more than two-thirds or even more than 90% of the particles.

[0021] The composite material is produced by mixing silicon particles with a carbon compound (preferably a carbohydrate or, in another preferred embodiment, a liquid or solid hydrocarbon) followed by a controlled thermal transformation or carbonization of the carbon compound. The term "thermal transformation" refers to the fact that the carbon compound undergoes one or more of the following changes, in particular by the thermal treatment in step A: polymerization, change of mutarotation, inversion, caramelization, oxidation, separation of H2O, separation of OH groups, condensation reactions, formation of intramolecular covalent bonds, redistribution, isomerization, partial pyrolysis, decomposition. The terms thermal treatment and temperature treatment are used synonymously. The "transition temperature" is the lowest temperature at which the compound undergoes this transformation under the conditions of the method according to the invention. Depending on the initial composition of the components of the composite material, there are various possible temperature ranges for choosing the temperature of the temperature treatment step A. After the transformation of the carbon compound in the thermal treatment step A is completed, usually with a loss of mass relative to the carbon compound used, the thermally treated intermediate product is in a different chemical and / or mechanical state for the second thermal treatment step B. This other condition also influences the reactivity of the initial components after the heat treatment step A to interact with (other) components inside the systems and tools used for the thermal transformation. The term "carbonization" refers to the fact that the carbon-containing intermediate product generated from the thermal transformation of the carbon compounds by heat treatment, in particular in step B, undergoes one or more of the following changes: pyrolysis, separation of water vapor, separation of OH groups, separation of CO, separation of CO2, separation of H2, separation of hydrocarbon compounds. In the heat treatment step B, it may be advantageous that the reaction gases that arise or escape from the heat treatment step A are vented and / or actively removed. It is further advantageous if, after the heat treatment step A, the transformed components, i.e. the silicon particles and the at least one carbon compound, no longer interact with the container or transport means from the heat treatment step A in the second heat treatment step B. It may be advantageous to transport the heat-treated intermediate product (after the heat treatment step A) to other containers or transport devices with different interaction properties for the heat treatment step B.In particular, it may be desirable and advantageous for no or only minimal material reactions of the resulting silicon-carbon composite material to take place in the heat treatment step B with objects or solids with which the resulting silicon-carbon composite material comes into contact during the heat treatment step B. It is thus possible to further avoid the generation or leakage of reactive gases, which are harmful or detrimental to these materials, into the walls surrounding or separating the heated spaces for thermal conversion or into the walls used for transporting the materials.

[0022] Thermogravimetry with downstream mass analysis of evolved or escaping reaction gases can be used to adjust the appropriate temperature ranges for the thermal treatment steps A and B. Furthermore, the gas atmosphere can be adjusted in a targeted manner during the method via the studied temperatures and thermal treatments.

[0023] The process temperature in the second heat treatment step of the thermal synthesis process, as well as the optional processes (milling, deagglomeration, rolling, crushing, fragmentation, mixing) to produce the desired particle size distribution, affect the size of the specific active surface. Additionally, the synthesis temperature can be selected to eliminate any oxides (SiO x ) carbothermally (for example as a result of generating carbon monoxide) or by choosing another reducing atmosphere. Whether this is desired or not, carbides can be produced on the surface of the silicon particles. Evidence of the formation of carbides is provided by XRD in the case of high synthesis temperatures of 1300 ° C. The carbon can also take the structure of synthetic graphite in some cases. A further optional measure of the method according to the invention provides for the grinding of the intermediate product of the first heat treatment step to the defined particle size of the final product (or to a suitable intermediate size) before the second heat treatment step (also: high temperature process step). This has advantages when carrying out high temperature process steps. Prior to the high temperature process steps the material is less hard and easier to grind, this is also especially true for materials having carbohydrates as the carbon source, which tend to form very hard composite particle agglomerates after both heat treatment steps. As a result of the particle size distribution that can be predefined in the milling process, subsequent high temperature process steps become more reproducible and the selection of the appropriate production system for production methods suitable for mass production becomes greater; in particular, subsequent printing or slot nozzle coating methods require a suitable starting particle size distribution in the printed paste, slurry, hot melt composite, or ink. Especially when using rotary furnaces, the temperature-time profile can be better and more reproducibly controlled in the through-feed process and, moreover, by the first heat treatment step A (i.e. conversion), it is possible to avoid undesirable separation products from concentrating in the gas atmosphere and negatively influencing the outcome of the high-temperature treatment, and therefore also to avoid an increasing accumulation of residues on the inner tube walls of the furnace. The surfaces of the ground particles can be flushed more uniformly and better by flashing / treating gases in high temperature process steps. The separation products during the thermal conversion can be extracted and transported better and more reproducibly, and undesirable secondary reactions with these separation products can be avoided or minimized.

[0024] The milling process after the second heat treatment step can, depending on the method, undesirably form new open silicon surfaces and adversely affect the composition or structure of the Si / C composite particles, thereby impairing battery function. This can be suppressed or minimized by proper milling of the Si / C composite material after step A.

[0025] When using a hydrocarbon as carbon source, on the one hand, the oxidation of silicon in both heat treatment steps can be minimized or inhibited, and possibly even existing surface oxides can be removed. Furthermore, when the hydrocarbon, for example paraffin, is appropriately selected, the formation of very hard, larger, compactly adhering particle agglomerates can be avoided. Thus, a milling step between the first and second temperature treatment is no longer necessary. However, it may also be necessary to feed the intermediate product in another container or, for example via a transport process, as bulk material into the rotary furnace to be sent to the second temperature treatment step. In this case, when a hydrocarbon is used as carbon source and dispersing medium, the deagglomeration or grinding of the composite bulk material preferably occurs automatically.

[0026] The method comprises the following steps. - mixing silicon particles with at least one carbon compound, - heat treating the mixture in at least two steps in the following order: A. heat treating the mixture at a temperature that corresponds at least to the transition temperature of the carbon compound, in particular at a temperature in the range of 120° C. to 700° C., preferably 120° C. to 500° C., more preferably 120° C. to 350° C., to obtain a heat treated intermediate product; B. Heat treating the heat treated intermediate product at a temperature above 750° C. to obtain a silicon-carbon composite material, in which case carbonization preferably takes place and / or compounds or elements are separated from the intermediate product, which usually escapes in gaseous form and can be removed by suction. As the temperature increases, an increasingly ordered structure is further produced. [Brief description of the drawings]

[0027] [Figure 1] FIG. 1 compares the Raman spectra of the composite material according to the present invention according to Example V, and silicon and graphene nanosheets. [Diagram 2] FIG. 1 shows an XRD spectrum of graphene nanosheets. [Figure 3A] FIG. 13 shows the results of performance tests on the extent of secondary reactions of composite material modifications in battery test cells. [Figure 3B] FIG. 13 shows the results of performance tests on the extent of secondary reactions of composite material modifications in battery test cells. [Figure 4] FIG. 1 shows the degradation characteristics of unprotected and protected silicon in a battery test cell. [Diagram 5] FIG. 1 shows the specific discharge capacity of a battery cell according to the present invention in a half-cell test after multiple charging cycles. [Figure 6A] FIG. 2 shows an REM image of a silicon-carbon composite material obtained according to the present invention. [Figure 6B] FIG. 2 shows an REM image of a silicon-carbon composite material obtained according to the present invention, used for EDX measurements (described further below). [Figure 7] FIG. 2 shows the specific charge capacity of a battery cell according to the invention based on paraffin as the carbon compound in a half-cell test with multiple charge cycles. [Figure 8A] FIG. 2 shows the temperature-time profile of the TGA measurement process. [Figure 8B] FIG. 1 shows TGA profiles showing the mass change in percent starting from 100% starting synthesis mass as a function of the temperature reached for the synthesis of Si nanopowder, sucrose and a simple dihydric alcohol as dispersant in a mass ratio of 1:0.556:1.666 Si:sucrose:dispersant. [Figure 8C] FIG. 8C shows the results of mass spectrometry analysis of the exhaust gases leaking from the measurement chamber along with the nitrogen throughflow supplied to the measurement chamber, associated with FIG. 8B. [Figure 8D] FIG. 1 shows TGA profiles showing the mass change in percent starting from a starting synthesis mass of 100% as a function of the temperature reached for the synthesis of silicon nanoparticles (Si) from white oil (paraffin) with a mass ratio of 1:5 Si:paraffin. [Figure 8E]FIG. 8E shows the results of mass spectrometry analysis of the exhaust gases leaking from the measurement chamber along with the nitrogen throughflow fed to the measurement chamber, associated with FIG. 8D. [Figure 9] FIG. 1 shows the viscosity of a dispersion of silicon nanoparticles and white oil. [Figure 10] Figure 1 shows the carbon compounds found by XPS measurements on the surface of the synthesis products obtained from silicon nanoparticles and paraffin oil in a mass ratio of 1:4.3. Typical temperature treatment steps A and B were used, ensuring a nitrogen atmosphere for these starting materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] It is important that in the method according to the invention at least two heat treatment stages are carried out. This means that the treatment is carried out at at least two different temperatures, which does not necessarily require cooling between the stages. Conversely, further heating can also be carried out after the first heat treatment stage A without significant cooling in order to carry out the second heat treatment stage B. The terms "heat treatment stage" and "heat treatment step" are used synonymously in this specification. It has been found that in the case of gentle heat treatment, first to a temperature higher than the transition temperature and then above the temperature of the first stage, in the second heat treatment stage, particularly advantageous product properties can be achieved. Furthermore, the two heat treatment stages can be carried out in separate apparatuses or separate systems and / or vessels (e.g. furnaces), which is preferred according to the invention. This allows a continuous production method to be realized. It may be advantageous to spatially separate the two heat treatment steps from one another by the material composition of the starting materials, in particular by the choice of carbon compounds or dispersants, so that different process atmospheres, process pressures and different devices for removal by suction are used for generating or escaping the reaction gases in the two heat treatment steps. The incorporation or transport of the starting materials can also be carried out in different ways in the two heat treatment steps.

[0029] In particular, when using hydrocarbons such as paraffins, which can simultaneously function as carbon source and dispersant, it is advantageous to first process the dispersed silicon particles, if the interface between the dispersed silicon particles and the gas atmosphere is as large as possible, in order to facilitate the escape of generated or escaping reaction gases. As a result of this, significant gradients in the interaction between the synthesis products and the gas atmosphere are avoided, which ensures approximately homogeneous material properties along the height of the vessel or along the gradients that occur.

[0030] If the dispersed silicon particles are initially applied as a thin layer onto a transport medium (e.g., on a continuous conveyor belt), then a continuous flat transport of the dispersed silicon particles along the temperature gradient is advantageous because the rapidly generated and escaping reaction gases can be uniformly evacuated or extracted or transported away from the heated system in which they are generated at any time.

[0031] At the end of the temperature treatment step A, the intermediate product thus produced can be recovered again, for example already as a powder with an approximately suitable particle size distribution. The recovery can be carried out, for example, in a container which can then be easily led into a second process chamber, in which on the one hand the high temperature treatment can be carried out, but on the other hand also with a completely different process atmosphere composition, process atmosphere pressure, as well as other transport or mounting concepts for the intermediate product which is further treated in the temperature treatment step B.

[0032] In one preferred embodiment, the powder-like intermediate product with a particle size distribution below 10 μm, more preferably below 3 μm, is first collected in a container from which it is transported in a second temperature treatment step B continuously and in a changed process atmosphere with negative or overpressure with respect to the ambient atmosphere into a high-temperature furnace, for example a rotary kiln. In this case, the powder-like intermediate product is transported continuously along the temperature gradient, preferably by heating to a higher process temperature or by cooling. In a further preferred embodiment, based on a rotary kiln, the rotation of the rotary kiln results in a continuous mixing of the powder-like intermediate product, with a simultaneous forward thrust by the adjustable tilt of the rotary kiln. In this case, the rotary kiln is preferably only partially filled, preferably to less than 50%, even more preferably to less than 30%, for the respective tube diameter along the complete rotary kiln axis. As a result, the generated or escaping reaction gases can rapidly escape. Furthermore, the positioning of the lance in the rotary kiln above the product allows the arrangement of different gas supply and extraction points at various points along the thrust movement. This allows any reaction gases that are generated or that escape to be extracted already where they are generated and not just escape at high temperatures.The materials of the rotary kiln are desirably selected so as not to adversely interact with the rotary kiln with which the intermediate product comes into contact during the second temperature treatment or to destroy the rotary kiln.

[0033] Furthermore, the two separate heat treatment stages A and B allow for a possible intermediate treatment of the heat treated intermediate product after the first heat treatment stage, such as for example milling of the heat treated intermediate product, the milling step being advantageously carried out in a separate system or apparatus, preferably after cooling.

[0034] In a preferred embodiment, depending on the starting composition of the synthesis product and / or depending on the proportion of carbon compounds and / or any further materials in the synthesis, such as lithium or lithium-containing compounds, in the case of a controlled atmosphere, controlled temperature control and controlled extraction, a milling step is carried out between temperature treatment A (conversion) and temperature treatment B (high temperature step) so that the intermediate product always remains under these well-controlled conditions, and a controlled or integrated transport is carried out between temperature treatment A and temperature treatment B, i.e. a comminution step (for example by milling). However, in particular, preferably, neither pressure conditions that deviate significantly from atmospheric pressure nor process steps that are demanding in terms of equipment (such as spray drying) are required, so that a production method with relatively low costs in terms of equipment is possible.

[0035] In one embodiment, at least step B, and optionally also step A, is carried out in a substantially oxygen-free atmosphere, in particular in a process gas atmosphere with less than 100 ppmv, less than 10 ppmv, less than 1 ppmv, or less than 0.1 ppmv O2. The atmosphere can be an inert gas atmosphere, in particular a nitrogen or noble gas atmosphere. However, other atmospheres are also possible, for example reducing atmospheres with hydrogen and / or carbon monoxide. A reducing atmosphere has the advantage that it can reduce silicon oxide or reduce oxidation. When silicon comes into contact with air, especially at high process temperatures, it very quickly forms a SiO2 layer on the silicon surface. In one embodiment, this SiO2 layer is reduced in size or is only very thin, in particular is substantially absent. A low-oxygen atmosphere can be used as an alternative to a substantially oxygen-free atmosphere, in particular with a proportion of O2 less than 5 vol.% or less than 1 vol.%. Instead of or in addition to a low-oxygen or substantially oxygen-free atmosphere, a process liquid can be used that can prevent silicon from coming into contact with air. In one preferred embodiment, a hydrocarbon-based process liquid, such as paraffin or paraffin oil, is added to the mixture of silicon particles and at least one carbon compound to minimize or completely avoid contact of the dispersed solid content with air and / or oxygen and / or nitrogen and / or humidity and / or other undesirable gases, such as evolved or escaping reaction gases. In this case, the process liquid wets the solid components of the dispersion and only leaks out completely if the temperature increases or the process atmosphere changes during temperature treatment step A (conversion process), but preferably only during temperature treatment step B. In a more preferred embodiment, the mixing of the silicon particles with the carbon compound and optionally other synthetic starting materials is carried out in a low-oxygen or substantially oxygen-free atmosphere and / or in the process liquid itself.

[0036] Preferred atmospheres include or consist of nitrogen, carbon dioxide, carbon monoxide, hydrogen, a noble gas, e.g. argon or helium, or mixtures thereof. Preferred process liquids are liquids suitable for keeping atmospheric oxygen away from the silicon surface. Particularly suitable are substances that are liquid at room temperature (20° C.) and / or in which the carbon compound has a solubility of at least 1 g / L, in particular at least 10 g / L or at least 50 g / L at 20° C. Suitable liquids are liquid at room temperature and atmospheric pressure and wet the silicon and / or silicon oxide surfaces. In one embodiment, the liquid can be mixed with water, i.e. such that the liquid forms a single liquid phase with water at room temperature.

[0037] Preferred liquids dissolve the carbon compounds in the mixture, in particular completely. Preferred process liquids are water, monohydric or polyhydric alcohols, such as isopropanol or ethanol, in particular dihydric alcohols, such as ethylene glycol, or mixtures thereof. Particularly preferred process liquids are based on paraffins. Process liquids are preferably used that have a higher evaporation temperature than the transition temperature of the carbon compounds. For example, if carbohydrates, such as sugars, form the main carbon source, correspondingly selected liquid hydrocarbons are used. The process liquid preferably provides good wetting of the silicon particles with the carbon compounds or the converted carbon compounds. In one preferred embodiment, water is not used, since water promotes the oxidation of silicon. The skilled person is able to select a suitable process liquid. In one embodiment, the mixture is produced without the addition of liquid. In that case, the mixture comprises silicon and at least one carbon compound, for example a hydrocarbon, such as paraffin, toluene, etc. In one embodiment, a dispersant is used that is not evaporated or is not completely evaporated at the end of the first heat treatment step (step A). If the dispersant is not completely evaporated, the comminution of the heat-treated intermediate product can be carried out at low cost and, in the case of paraffins or other suitable hydrocarbons, even with the exclusion of atmospheric influences.

[0038] In one alternative preferred embodiment, paraffin is used as process liquid, which is solid at room temperature and becomes liquid at moderate temperatures, preferably between 30°C and 90°C, at which temperatures it serves to disperse the components accurately and solidifies again after dispersion, preferably with the exception of oxygen. As a result of this, for example, lithium or lithium-containing starting materials can be contained in the dispersion without reacting with acids, nitrogen and / or water vapor or moisture in the air. After cooling and solidifying the dispersion, it can also be transported by air, indeed avoiding the risk or interaction of the lithium-containing compounds with the atmosphere. In particular, the highly exothermic reaction of lithium or lithium-containing starting materials with the potential consequences of fire can be suppressed and avoided in this way.

[0039] In one preferred embodiment, after the first heat treatment step, at least 10% by weight, in particular at least 20% by weight, of the dispersant used is still present. Dispersants with a boiling point at normal pressure above 120° C., in particular above 150° C. or above 160° C. or above 180° C. are preferred. The process liquid and the dispersant may be the same or different. In one embodiment, after the end of step A, at least 90% by weight, in particular at least 95% by weight or at least 99% by weight of the dispersant and / or the process liquid is no longer contained in the intermediate product, in particular evaporated or reacted out.

[0040] Cooling after step B and / or after step A is also preferably carried out in an oxygen-low or substantially oxygen-free atmosphere, such as an inert gas atmosphere, in particular a nitrogen or noble gas atmosphere or a reducing atmosphere. A further preferred embodiment uses a reducing atmosphere (hydrogen or carbon monoxide content).

[0041] In one embodiment, at least one additive is added to the mixture. Suitable additives include structuring and / or catalytically acting additives, in particular additives selected from graphene, graphene oxide, graphite, fullerenes, nanotubes and combinations thereof. Suitable catalytic additives can alternatively or additionally be selected, for example, from different iron compounds or contain other catalytic additives known to the skilled person. These additives can be present in the mixture in a proportion of 0.01 to 10.0% by weight, in particular 0.05 to 5.0% by weight or 0.1 to 2.5% by weight. When these additives are added, the duration of the first and / or second heat treatment step and / or the temperature of the first and / or second heat treatment step can be reduced. The method can also be carried out without additives.

[0042] In one preferred embodiment, the mixture of starting materials may contain the following components: [Table 1]

[0043] In one embodiment, a dispersant is used in a mixture, the mixture containing the following components: [Table 2]

[0044] In a further embodiment of the mixture containing a dispersant, the mixture contains the following components: [Table 3]

[0045] In one alternative embodiment, no dispersant is used at all or only in very small amounts in the mixture, and the mixture contains the following components: [Table 4]

[0046] In a further embodiment of the mixture with low levels of dispersant or without dispersant, the mixture contains the following components: [Table 5]

[0047] In one alternative embodiment, no dispersant is used at all or only in very small amounts in the mixture, and the mixture contains the following components: [Table 6]

[0048] In a further embodiment of the mixture with low levels of dispersant or without dispersant, the mixture contains the following components: [Table 7]

[0049] In a further embodiment of the mixture with low levels of dispersant or without dispersant, the mixture contains the following components: [Table 8]

[0050] In one alternative embodiment, alternative liquid or solid carbon compounds from the category of hydrocarbons, particularly paraffins, are used in the mixture, which can simultaneously function as dispersants at room temperature or at least slightly elevated temperatures. [Table 9]

[0051] In one preferred embodiment of the aforementioned alternative embodiment, the mixture of starting materials may contain the following components, where paraffin is used as the carbon compound and dispersant: [Table 10]

[0052] In a further preferred embodiment of the aforementioned alternative embodiment, the mixture of starting materials may also contain sucrose in addition to silicone and paraffin. [Table 11]

[0053] In a further preferred embodiment of the aforementioned alternative embodiment, the starting material mixture may also contain a suitable lithium compound in addition to silicon and paraffin, where the mass ratio of Si and Li atoms is between 1:0.5 and 1:5.0. [Table 12]

[0054] The mixture used has a relatively high percentage of solids compared to the prior art. This refers to the percentage that remains as solids when the dispersant and / or process liquid evaporates. This is in particular the sum of the percentages of silicon, carbon compounds and optional additives. This percentage of solids can be at least 9.0% by weight, at least 16.5% by weight or at least 20.0% by weight relative to the mass of the mixture. The percentage of solids can be significantly higher still in variants with a low degree of dispersant or without dispersant. In mixtures containing dispersant, the percentage of solids is preferably up to 70.0% by weight or up to 60.0% by weight. In one preferred embodiment, the percentage of solids is even up to 90% by weight. In the case of an excessive percentage of solids, it is more difficult to achieve a uniform distribution of the carbon compounds on the silicon. Also, if the percentage of dispersant is too high, a lot of time and energy is required to remove the dispersant. Moreover, a high percentage of dispersant should be avoided from the perspective of minimizing costs and emissions that may be harmful to the environment. Furthermore, in this case, there is also a risk that the silicon particles will be further oxidized on their surface. This method does not rely on the use of spray drying, so it can achieve a relatively high solid content, and can reduce energy requirements, capital investments, and the use of solvents.Therefore, the mixture is preferably not spray-dried, and in particular the entire manufacturing process is managed without spray drying, and uses highly viscous dispersions that are not suitable for spray drying at all.In this case, the proportion of dispersing agent is reduced to such an extent that it is still possible to easily disperse starting material, but allows the escape of reaction gases that are generated or leak, and at the same time minimizes the cost of dispersing agent and any post-treatment.

[0055] The dispersant also has the function of ensuring as homogeneous a distribution of the carbon compound on the silicon as possible, so that the ratio of these two components is important. The mass ratio of carbon compound to dispersant can be used in the range of 0.1-0.7, in particular in the range of 0.1-0.4 or 0.3-0.7. These ratios have been shown to be advantageous. In one embodiment, the aim is to keep the proportion of dispersant as low as possible so that a sufficiently homogeneous dispersion can still be achieved. In one preferred embodiment, very high viscosities of the mixture, in this case above 5000 mPa·s, in particular above 15000 mPa·s or above 25000 mPa·s, are desirable for dispersion purposes. In one embodiment, the viscosity does not exceed 50000 mPa·s. In particular, the viscosity decreases with increasing shear rate (shear thinning). A small amount of dispersant has a positive effect on the cost of the method, the environmental friendliness of the method, as well as avoiding undesirable parasitic oxidation of particles in the outgassing of oxygen-containing removal or outgassing products of the dispersant during the heat treatment stage.

[0056] The viscosity can be measured, for example, at 21.5° C. using a rotational viscometer (plate / plate with a gap width of 0.3 mm, counter-rotation, shear rate 100 / s).

[0057] It has been found that silicon-carbon composites have excellent properties when used as or in anode materials for lithium-ion batteries, especially in terms of efficiency in the first operating cycle (first cycle efficiency), as well as in terms of the non-toxic and environmentally friendly binders and solvents that can be used. In one embodiment, this advantage is potentially linked to the fact that the silicon has substantially no or only a thin layer of silicon dioxide in the region of the interface with the carbon.

[0058] XPS measurements (X-ray photoelectron spectroscopy) showed that silicon carbide is not present on the surface (Figure 10). Furthermore, the XPS results show that the SiO2 particles on the surface are functionalized with graphite, but that the SiO2 particles on the surface are not fully functionalized with graphite. This finding is related to the fact that the graphite layer is with a high probability less than 3 nm thick, and consequently, certain areas of the Si surface that were originally oxidized are detected, leaving a thin oxide layer.

[0059] When this material is used in a battery cell, Li + The formation of lithium silicate, which has poor ion diffusion properties, is potentially suppressed by reducing the amount of SiO2 in this region.Furthermore, providing such a simple method for silicon-carbon composites is one of the achievements of this invention.

[0060] The silicon used as starting material includes silicon particles.Porous or porosified silicon particles known per se to those skilled in the art are also possible as silicon particles.Silicon can be amorphous or crystalline silicon, in particular polycrystalline silicon.Silicon can be used with a particle size D90 of less than 300nm or less than 200nm.

[0061] Silicon having at least one partial surface composed of silicon dioxide can be used as starting material for the method. In particular, silicon particles are considered which have an oxide layer formed on their surface as a result of contact with an oxidizing environment. The method optionally comprises a step of removing the silicon dioxide from the surface of the silicon. This can be done, for example, by milling, plasma treatment and / or etching. Alternatively or additionally, a reducing atmosphere can be used for this purpose.

[0062] Etching to remove silicon dioxide is preferably performed using an acid or base. Preferred substances are HF, KOH, NHF, NHHF2, LiPF6, H3PO4, XeF2, SF6 and mixtures thereof. HF is particularly preferred. The acid or base can be mixed with structuring or catalytically acting additives (e.g. metal-assisted etching). In one embodiment, a plasma treatment is used to remove the oxide layer. In one embodiment, etching is used during the thermal treatment, particularly during step A.

[0063] The silicon preferably used here is elemental silicon, in particular in the form of silicon particles. The silicon particles can optionally have further substances, in particular other metals, oxides, carbides or doping agents (in particular phosphorus, boron, gallium or aluminum, which increase the electrical conductivity of silicon), preferably in small amounts, such as at most less than 10% by weight, particularly preferably less than 1.0% by weight. In one embodiment, the silicon particles are composed of elemental silicon, silicon oxide, or binary, ternary or multi-element silicon / metal alloys (e.g. with Li, Na, K, Sn, Ca, Co, Ni, Cu, Cr, Ti, Al, Fe). In one preferred ... x Li y The particles can be produced from Si particles, for example in a paraffin dispersion, at relatively low temperatures, preferably with the exclusion of oxygen, nitrogen and water vapor. x Li y The particles are preferably generated during the temperature treatment step A. In this case, Si x Li y A proportion of Li up to 35% by weight of the alloy is preferred, even more preferred between 10 and 30% by weight.

[0064] Silicon preferably has at most small amounts of contaminants, in particular less than 10% by weight, particularly preferably less than 1.0% by weight of contaminants (such as B, P, As, Ga, Fe, Al, Ca, Cu, Zr, C, etc.). Phosphorus, boron, aluminum, tin, antimony and / or gallium can be added for the purpose of improving the conductivity of the Si particles. In one preferred embodiment, the silicon is 1 cm 3 per 10 15 ~10 21 has a typical dopant concentration in the range of dopant atoms. For certain applications, it is advantageous to dope the silicon. In one preferred embodiment of this method, the proportion of the corresponding dopant is added to the mixture of silicon particles and at least one carbon compound already during the heat treatment A or alternatively during the heat treatment B. From the perspective of an economical method, the addition of aluminum is particularly advantageous because Al-doped Si particles can be produced at a temperature above 577 °C, i.e., the eutectic temperature, or at a temperature above 660 °C, the melting point of Al.

[0065] When the silicon particles contain silicon oxide, the stoichiometry of the oxide SiO x is preferably in the range of 0 < x < 1.3. When the silicon particles contain silicon oxide with a higher stoichiometry (for example, x = 2), the layer thickness on the surface is preferably less than 10 nm.

[0066] In the case of an alloy of silicon particles and a metal M (such as an alkali metal), the stoichiometry of the alloy M y Si can be in the range of 0 < y < 5. The silicon particles can be alloyed with lithium. In this case, the stoichiometry of the alloy Li z Si is preferably in the range of 0 < z < 2.2. However, in another preferred embodiment, a Li z Si alloy in the range of 2 < z < 4.3 is used.

[0067] The alloying of silicon and lithium can also be carried out in one preferred embodiment first during the temperature treatment step A or B. One important thing to note here is the form in which the lithium source is added before the respective temperature treatment step of the synthesis, and how it interacts with the respective process atmosphere or dispersant or other synthesis components. For example, if pure lithium is added to the synthesis or dispersion, it should be strictly ensured that the lithium does not react with oxygen, nitrogen or even water vapor. This can be avoided, for example, by the fact that the lithium is handled wet with paraffin oil as dispersant. Additionally or alternatively, at least step B, and optionally also step A, are carried out in a substantially oxygen-free, nitrogen-free and anhydrous steam atmosphere, or in an atmosphere having in each case less than 100 ppmv, preferably less than 10 ppmv, preferably less than 1 ppmv or less than 0.1 ppmv of O2, N2 or H2O.

[0068] In order to achieve alloy grain sizes in the micrometer or submicrometer range after the temperature treatments of steps A and B, it is desirable that at least one of the alloying partners is present in the initial state, i.e. with a small particle size before the temperature treatment, finely dispersed, and ideally both alloying starting materials are present. Depending on the melting point of the lithium source and depending on the dispersing agent used, it may be advantageous to first carry out the carbon coating of the silicon particles in the temperature treatment step A and to add only the lithium source in the temperature treatment step B. A large number of lithium starting materials are possible as lithium sources for such alloy synthesis. In addition to lithium itself, lithium salts, such as lithium halides, in particular lithium bromide, lithium hydride, lithium hexafluorophosphate, lithium stearate, lithium nitride, lithium amide, lithium carbide and lithium soaps are particularly suitable.

[0069] In one preferred embodiment, the silicon particles are composed of at least 90% by weight (especially ferrosilicon), preferably at least 95% by weight, preferably at least 98% by weight of silicon (especially metallurgical silicon) based on the total weight of the silicon particles. The silicon particles are preferably substantially free of carbon.

[0070] In one embodiment, silicon particles can have Si-OH or Si-H groups on the surface, or covalently bound organic groups, such as alcohols or alkenes, etc. Thus, the wetting properties of liquid components, such as dispersants or liquid carbon compounds, can be influenced in a targeted manner during synthesis.

[0071] Moreover, in order to suppress the formation of a solid electrolyte boundary layer and / or improve the lithium transport properties, it is possible and advantageous under certain circumstances to apply coatings in a targeted manner using methods such as ALD (atomic layer deposition), PVD (sputtering, vapor deposition), CVD (chemical vapor deposition) or PECVD (plasma enhanced CVD). The coatings may include, inter alia, aluminum oxide, titanium oxide, zirconium oxide, silicon carbide and / or other carbon-containing (also organic) or Li-containing coatings. Such coatings are possible both before and after the heat treatment step, or even on the anode surface after the last step for the adjustment of the particle size distribution and their completion. In the case of powder type particles, the fluidized bed ALD method is preferred, in which case the leakage of the particles is minimized by the appropriate construction of the fluidized bed reactor.

[0072] Furthermore, Li-containing components or lithium itself, particles or liquids can be added to the mixture or intermediate product before step A and / or step B with the aim of being able to produce a lithium-silicon alloy during the temperature treatment. Suitable components can be selected from the group consisting of Li salts, such as LiF, LiCl, LiBr, LiI, Li3N, LiNH2, LiPF6, or Li2CO3; lithium hydrides, such as LiH, LiBH4, LiAlH4; organolithium compounds, such as n-butyllithium, t-butyllithium, methyllithium and phenyllithium, lithium diisopropylamide, lithium bis(trimethylsilyl)amide; lithium soaps and combinations thereof. In particular, in one embodiment, the Li-containing component can also be added to the produced composite material only at or after the end of the second temperature treatment step B, and before the third temperature treatment. This requires good control of the gas atmosphere, in particular a substantially oxygen-free, nitrogen-free, and anhydrous or anhydrous steam atmosphere, during and after the first two temperature treatment steps A and B, and potential further temperature treatment steps.

[0073] The carbon-coated lithium-containing composite particles should further be protected from potential undesired reactions with the atmosphere or binder after temperature treatment. This can be achieved by further processing and / or storage in a protective or inert gas atmosphere, in vacuum, or in a dispersion with a suitable liquid or binder that inhibits undesired reactions.

[0074] In one embodiment, the method of the invention offers the possibility of producing silicon-carbon composites with a layer of silicon dioxide (SiO2) of reduced thickness between the silicon and the carbon. The silicon particles can be optionally pretreated in HF or another fluorine compound to remove silicon oxide before the mixture with the carbon compound is produced. The silicon particles can then be directly mixed with a liquid carbon compound or dispersant, such as paraffin, to undergo a heat treatment. The method can be carried out with the exclusion of air, in a low-oxygen or substantially oxygen-free atmosphere. In one preferred embodiment, the silicon particles are transferred into a hydrofluoric acid (HF) dispersion, followed by a dispersion with liquid paraffin in a suitable container, before mixing with at least one carbon compound and before the heat treatment of the mixture to remove oxides on its surface. As expected, a complete phase separation occurs between the HF and the silicon particles dispersed in the paraffin. The HF can then be separated, for example, via a filter.

[0075] The carbon compounds are suitable for forming carbon-containing coatings on the surface of silicon, in particular coatings containing or consisting of structured carbon. The compounds are characterized in that they form carbon, in particular at least partially structured carbon, during the heat treatment described herein. Preferred carbon compounds in the context of the present invention are carbohydrates, in particular sugars, as well as mixtures of different carbohydrate or hydrocarbon compounds that are solid or liquid at room temperature. In a preferred embodiment, the carbon compounds are selected from monosaccharides, disaccharides and polysaccharides and mixtures thereof. Preferred sugars used as carbon compounds in the context of the present invention are glucose, fructose, galactose, saccharose, maltose, lactose, starch, cellulose, glycogen or mixtures or polymers thereof.

[0076] Other biopolymers such as lignin can be used alternatively or additionally as carbon compounds, so that crude oil-based products can be largely avoided. The carbon compounds are preferably not polymer plastics. As carbon compounds, renewable raw materials are preferably selected that are available in the desired / necessary amounts without causing environmental damage and at low material costs. Thus, for example, the carbon compounds are preferably selected from the list of waxes, vegetable oils, fats, oils, fatty acids, rubbers and resins.

[0077] In one preferred embodiment of the method, the carbon compound alternatively or additionally comprises at least one carbon compound selected from the list of lignin, wax, vegetable oil, fat, oil, fatty acid, rubber and resin, which is also advantageous from the point of view of biocompatibility to avoid environmental damage and minimize environmental burden.

[0078] In another preferred embodiment, the carbon compound is a paraffin or a related hydrocarbon. The combination of silicon particles with paraffin as the carbon compound is advantageous because it allows a significant shortening and simplification of the process, i.e. a milling step is no longer necessary as an intermediate step.

[0079] The term "structured carbon" is known to those skilled in the art. This term includes, among others, graphene, graphene oxide, carbon nanotubes, fullerenes, aerographite, "hard carbon" and graphite.

[0080] The amount of carbon compound is preferably selected so that a carbon to silicon mass ratio of 3:1 to 1:90, in particular 3:1 to 1:20, more preferably 1.2:1 to 1:10, particularly preferably about 1:5 or about 1:9 is produced in the composite. The coating on the silicon preferably comprises two or more carbon layers, in particular at least two carbon layers, at least three carbon layers or at least five carbon layers. According to the invention, the aforementioned mass ratio is preferably achieved in that the mass proportion of the carbon compound in the mixture is either 5% to 110% of the silicon mass or 1000% to 200% of the silicon mass. In a preferred embodiment, the aforementioned mass proportion in the mixture is 25% to 80%, in particular 35% to 70%, particularly preferably 40% to 60% with respect to the silicon mass. The selection of the appropriate amount of carbon compound contributes to obtaining the desired configuration of the silicon-carbon composite.

[0081] In a preferred embodiment, in which a liquid hydrocarbon, such as paraffin, is used as the sole carbon source and simultaneously as a dispersant, the mass proportion of the carbon compound in the mixture is 1000% to 100% of the mass of silicon. For example, 15 mL of paraffin are mixed with 3 g of Si. The indicated range of liquid hydrocarbon is necessary to ensure good dispersion with the silicon particles, but also because a high proportion of the liquid hydrocarbon leaks out during the heat treatment. The proportion of the carbon source is preferably selected so that it is just sufficient to allow the silicon particles to be easily dispersed therein. Here, other materials can also be added to the mixture. When using a hydrocarbon such as paraffin, this can also be, among others, a compound containing lithium or elemental lithium. Because, as a result of the use of paraffin, air is excluded during mixing and dispersion, which makes it possible to avoid undesirable reactions of the lithium compound with nitrogen, oxygen and / or air moisture or water vapor.

[0082] In one preferred embodiment, where paraffin is used as the sole carbon source and simultaneously as a dispersant, the mass ratio of paraffin to silicon is in the range of 1:1 to 10:1, preferably in the range of 3:1 to 6:1. After the heat treatment steps A and B, a silicon-carbon composite is produced in which the silicon mass fraction is usually more than 80%, preferably more than 90%, more preferably more than 95%, most preferably more than 99%. In a further preferred embodiment, where lithium compounds or lithium are additionally used in the starting synthesis, their proportions are usually selected so that the composite after synthesis contains an atomic ratio of Li to Si of 0.5:1 to 4:1, preferably 1:1 to 3:1. The use of a hydrocarbon, such as paraffin, as a carbon source and simultaneously as a dispersant is advantageous, since it allows the heat treatment to be separated into two separate temperature treatment steps A and B, and the intermediate cooling and milling processes after the first temperature treatment to be omitted. The two temperature treatment steps A and B may be separated spatially and / or temporally in order to separately remove substances generated and leaking during the heat treatment process A without adversely affecting the gas atmosphere of the second heat treatment step B. A further advantage is that the processing time in the case of separate heat treatment steps can be significantly reduced.

[0083] In another preferred embodiment where both a carbohydrate (such as sucrose) and paraffin (the latter as a dispersant and carbon source) are used to produce silicon-carbon composites with the exclusion of air, a small amount of paraffin is added for dispersion purposes, appropriate to allow dispersing of viscous dispersions that are not suitable for spraying.

[0084] In one preferred embodiment, the mixing step comprises contacting the silicon surface or silicon oxide surface with a carbon compound. The mixing can comprise dispersing silicon particles in a dispersant / process liquid. In particular, this step comprises the production of a dispersion, a carbon compound, silicon and a dispersant. In this case, the silicon is contacted with the dispersion, in particular by incorporating the silicon in the dispersant or by applying the dispersion onto the silicon. The incorporation of silicon into the dispersion can be carried out before or after together with the carbon compound. Thus, in this preferred configuration of the method according to the invention, in addition to the dispersant, there is a dispersion comprising a carbon compound and silicon. The silicon can in particular be a plurality of silicon particles. This allows for a particularly simple and cost-effective method. In one preferred embodiment, the carbon compound is dissolved in the dispersant and the additive, such as structured carbon, as well as the silicon particles are dispersed therein. In one configuration of the method, the contacting step is carried out before the optional step of milling the mixture, the dispersant preferably being capable of acting as a milling medium and a protective fluid during milling.

[0085] The use of the dispersions described above has the advantage that the silicon surface is protected by the dispersing agent from the effects of atmospheric oxygen and other oxidizing atmospheres. The dispersing agent preferably functions in this context as a protective fluid. The dispersing agent further ensures a uniform distribution of the carbon compounds on the silicon. In one preferred configuration, the dispersing agent is partially or completely removed in a heat treatment step A, and the carbon compounds are precipitated on the silicon surface and at least partially converted. A heat treatment step B can then be advantageously carried out as described above in order to convert the carbon compounds precipitated on the silicon surface into a carbon-containing coating. In particular, the carbon compounds are converted such that other elemental components other than carbon and silicon, and also lithium if a lithium source is used in the starting compound, are largely removed from the resulting composite, and structured carbon compounds are formed in close contact around the surface of the silicon particles, if possible, or are similarly structured Si-Li-C alloys if a lithium source is present in the starting compound. The term "substantially removed" may in particular be understood as meaning that the proportion of components in the composite that are not carbon or silicon, and possibly not lithium, is at most 15% by weight, at most 10.0% by weight, at most 5.0% by weight, at most 3.0% by weight, or at most 1.0% by weight.

[0086] The silicon may advantageously be a body or a particle or a majority of a particle, the surface of which is at least partially, in particular at least 90% or at least 95%, in particular substantially completely, composed of silicon and / or silicon oxide. The body or particle is preferably composed of silicon.

[0087] Silicon may have a particle size D90, in particular less than 500 nm or less than 300 nm. In one embodiment, the particle size D90 is at least 50 nm. The particle size can be determined, for example, by dynamic light scattering or by REM. In the case of spherical particles, the particle size corresponds to the diameter of the particle. In this case, the value D90 represents the point in the particle size distribution at which 90% of the particles have a particle size smaller than or equal to D90. Other D values ​​should be understood similarly. When the D value relates to a mass distribution, D90 means that 90% of the total particle mass is composed of particles that are equal to or smaller than the D90 value. Other D values ​​should be understood here similarly. Unless otherwise indicated in this specification, the D value relates to the distribution of the number of particles.

[0088] [Heat treatment] The temperature in step A is higher than the transition temperature of the carbon compound, in particular at least 5° C., at least 10° C. or at least 20° C. higher than the transition temperature of the carbon compound. If a mixture of different compounds is used as the carbon compound, the temperature in step A is higher than the transition temperature of the compound having the highest transition temperature. In particular, the temperature in step A is higher than the temperature in step B. The temperature in step A can be between 120° C. and 700° C., preferably between 120° C. and 500° C., even more preferably between 120° C. and 350° C., and can be in the range between 150° C. and 250° C. In one embodiment, the temperature is between 175° C. and 200° C. and / or above 180° C. in step A. The temperature during the heat treatment does not have to be constant for a particular temperature, but can assume other values ​​or can vary temporarily around the set value as a result of planned or technically induced deviations. However, in the context of the present invention, the heat treatment provides that the mixture in step A is exposed to a temperature within the aforementioned limits for at least a certain time, in particular the time described herein. This can be carried out, for example, in a furnace. It is not excluded that the heat treatment according to step A initially consists of a first period of treatment at the indicated temperature conditions and then of a second period of treatment, as long as it is ensured that the temperatures and times described herein are generally satisfied. Nevertheless, it is preferred that the heat treatment according to step A is carried out in one step, i.e. without the minimum temperature being undershot during step A.

[0089] The heat treatment according to step A is preferably carried out under a pressure of 95 to 110 kPa, in particular under atmospheric pressure. In an alternative embodiment, this step can be carried out at high pressures, in particular in the case of overpressures of more than 5 Pa, in particular more than 5 kPa or more than 15 kPa, compared to the ambient pressure. When operating in a low-oxygen or substantially oxygen-free atmosphere, overpressure can be applied to block the ambient atmosphere from the furnace used. Also, a higher pressure can save energy, since a higher pressure can affect the enthalpy. In this embodiment, an overpressure of 10 to 1000 kPa compared to the ambient pressure is desirable. In a further embodiment, step A is carried out in the form of hydrothermal carbonization. In this case, particularly high process pressures are used, in particular higher than 0.5 MPa. The energy requirements for process step A can be reduced in the case of appropriate process management.

[0090] In another preferred embodiment, a negative pressure is desirable compared to the ambient atmosphere or even a vacuum. This requires that the furnace interior is hermetically sealed from the ambient atmosphere and has the advantage that the process atmosphere inside the furnace can be kept almost oxygen-free or low in oxygen, even if outgassing occurs during the conversion, decomposition or carbonization process. The outgassing products separated from the original carbon compounds are consequently immediately extracted and vented to the atmosphere surrounding the process material. Typical pressures are preferably 0.01 to 95 kPa absolute. In one embodiment, the negative pressure is at least -5 kPa or at least -15 kPa compared to the ambient pressure. The use of negative pressure can also optionally replace the effect of a protective atmosphere.

[0091] In one embodiment, the indicated temperature in step A is maintained for a period of at least 1 minute or at least 5 minutes, in particular between 5 minutes and 1000 minutes. The heat treatment step A is preferably carried out for a duration of at least 15 minutes, in particular at least 25 minutes, or at least 1 hour, or at least 2 hours, particularly preferably at least 5 hours or at least 12 hours. A minimum duration is recommended to ensure partial or complete removal of liquid or substantial conversion of carbon compounds. The heat treatment step A can be terminated after the completion of these processes. According to the invention, this is preferably after at least 20 hours, in particular at least 10 hours, preferably at least 6 hours or at least 2 hours.

[0092] The heat treatment according to step A serves to prepare the pyrolysis of the carbon compounds. In particular, during the corresponding heat treatment, potentially present solvents, possibly dispersants, milling media and / or process liquids are partially or completely evaporated and the carbohydrates used as carbon compounds or alternatively or additionally used carbon compounds are at least partially converted. Since significant local differences in the loading of the process atmosphere due to escaping substances can occur during the conversion of the carbon source and / or the leakage of solvents or dispersants, it must be ensured that these substances are properly evacuated from the inside of the furnace or the temperature treatment system and that the exhausted reaction gases are prevented from condensing in the delivery air flow as a result of cold surfaces and falling or flowing back into the interior of the thermal system. The condensates formed are further prevented from blocking or destroying the delivery air flow passages.

[0093] In one preferred embodiment of the method for a dispersed (starting) mixture of silicon particles and at least one carbon compound, the method comprises a step immediately following the application of the mixture on the entire surface and / or a thin layer onto a conveyor belt or another suitable transport medium. This has the advantage that the reaction gases escaping during the subsequent heat treatment of the mixture are rapidly transferred into the process atmosphere, without the initial flow of a large amount of the (starting) mixture. In a further preferred embodiment of the method, the method comprises an additional step of transporting the mixture during the heat treatment, in particular by one or more heat treatment systems. As a result of this, it is possible to locally extract, in a spatially separated manner and in a manner independent of the occurrence temperature, for example, the reaction gases escaping along the temperature-time profile of heat treatment A, so that in the case of a subsequent higher temperature there is a different atmosphere composition than in the case of a previously spatially passed lower temperature. This is particularly advantageous when water vapor or oxygen compounds are generated, since they are (can be) extracted in the case of a relatively low temperature, and then they can no longer lead to a possible oxidation of silicon or lithium at high temperatures.

[0094] The temperature in step B ranges from more than 750° C. to 2600° C. In particular, the temperature in step B exceeds the temperature in step A. In an embodiment, the temperature in step B is limited to at most 2000° C., or at most 1800° C., or at most 1400° C. The temperature in step B may be at least 800° C., at least 1000° C., more than 1000° C., or at least 1050° C. In an embodiment, the temperature is between 1000° C. and 1600° C., which may range from 1050° C. to 1500° C. The temperature in step B may be below the melting point of the silicon particles, in particular below the melting point of pure silicon. The temperature during the heat treatment does not have to be constant at a particular temperature, but may assume other values ​​or may vary temporarily around the set value as a result of planned or technologically induced deviations. In the context of the present invention, heat treatment nevertheless provides that the intermediate product heat treated in step B is exposed to an ambient temperature within the aforementioned limits for at least a certain time, in particular for a time as described herein. In one preferred embodiment, the temperature of step B is between 800°C and 1200°C, more preferably between 800°C and 1100°C. In one particularly preferred embodiment, the temperature of step B is adjusted such that substantially no formation of silicon carbide occurs. This is particularly advantageous when paraffin or paraffin oil is used as carbon source.

[0095] The heat treatment can optionally be carried out at a heating rate selected in a targeted manner relative to the desired target temperature in each step, for example to allow volatile components to escape first before the target temperature is reached. The preferred average heating ramp is between 1 K / min and 100 K / min, preferably between 2 K / min and 20 K / min, more preferably between 3 K / min and 15 K / min. The heat treatment can be carried out, for example, in a furnace. The maximum temperature in step B is in particular higher than the maximum temperature in step A. The heat treatment according to step B does not exclude the inclusion of a first period of treatment at the indicated temperature conditions and then a second period of treatment, as long as it is ensured that the temperatures and times described herein are met overall. Nevertheless, it is preferred that the heat treatment according to step B is carried out in one step, i.e. without the minimum temperature being undershot during step B.

[0096] The heat treatment in step B is preferably carried out at a pressure of 95 to 110 kPa, particularly at atmospheric pressure.

[0097] In an alternative embodiment, this step can be carried out at high pressure, especially in the case of an overpressure of more than 5 Pa compared to the ambient pressure. When operating in a low-oxygen or substantially oxygen-free atmosphere, an overpressure can be applied to seal off the ambient atmosphere from the furnace used. Also, higher pressures can affect the enthalpy, so energy can be saved by using higher pressures. In this embodiment, an overpressure of 10 to 1000 kPa compared to the atmosphere surrounding the heat treatment device is desirable.

[0098] In another preferred embodiment, a negative pressure is desired compared to the ambient atmosphere or even a vacuum. This requires a hermetic sealing of the interior of the furnace against the ambient atmosphere and has the advantage that the process atmosphere inside the furnace can also be kept almost oxygen-free or low in oxygen in case of degassing during the conversion, decomposition or carbonization process. The outgassing products separated from the original carbon compounds are then directly extracted and removed from the atmosphere surrounding the process material. Typical pressures are preferably 0.01 to 95 kPa absolute. In one embodiment, the vacuum is at least -5 kPa or at least -15 kPa compared to the ambient pressure.

[0099] In one preferred embodiment, the indicated temperature in step B can be maintained for a period of at least 1 minute or at least 5 minutes, in particular between 5 minutes and 600 minutes. In further embodiments, the duration of step B is at least 15 minutes or at least 25 minutes. The duration of step B can be limited to a maximum of 500 minutes or a maximum of 400 minutes. In one embodiment, the duration is a maximum of 150 minutes or a maximum of 90 minutes. In one preferred embodiment, the heat treatment step B follows the heat treatment step A, in particular the heating to the higher temperature of the second heat treatment step is carried out immediately after the first heat treatment step without intermediate cooling.

[0100] In another preferred embodiment, different furnaces are used for the first and second heat treatment steps. In one embodiment, the first heat-treated intermediate product is ground after step A but before step B. This facilitates or makes unnecessary an optional further grinding step after step B. This is particularly advantageous, since the composite material after step B is significantly harder and can only be ground at a very high cost. In one embodiment, the heat-treated intermediate product is partially or completely cooled (i.e. to room temperature 20° C.) after step A and before step B. In particular, for the transport of the intermediate product after the temperature treatment step A, it may also be advantageous to keep this intermediate product in a controlled process atmosphere, for example with the exclusion of oxygen, or even in a pure inert noble gas atmosphere (e.g. argon), or under negative pressure or vacuum. In one embodiment, the method comprises, after the heat treatment step A but before the heat treatment step B, a step of transporting the heat treated intermediate product with the exclusion of water vapor and / or oxygen, or a step of transporting the heat treated intermediate product in a pure noble gas atmosphere, e.g. argon, or a step of transporting the heat treated intermediate product under negative pressure or vacuum.

[0101] The minimum temperature indicated for the heat treatment step B should not be undershot in order to ensure a complete conversion of the carbon compounds into a carbon-containing coating. However, the maximum temperature indicated should not be exceeded in order to avoid the formation of carbides. The heat treatment step B is preferably carried out for a period of at least 30 minutes, in particular at least 90 minutes, preferably at least 180 minutes or at least 300 minutes. The heat treatment step B should be carried out for a period of not more than 15 hours, in particular not more than 10 hours, particularly preferably not more than 8 hours. When the correct time is selected, a multilayer of structured carbon is preferably obtained, preferably with substantially all OH groups separated.

[0102] A heat treatment step B preferably follows the heat treatment step mentioned above at a lower temperature. The heat treatment step A serves in particular the purpose of at least partially removing any liquid and at least partially converting the carbon compounds. The heat treatment step B preferably serves the purpose of at least partially converting the carbon compounds to structured carbon and pyrolysis or carbonization of the carbon compounds remaining after step A. The indicated temperature ranges have been shown to be advantageous since substantial conversion is achieved and the formation of silicon carbide (SiC) is reduced or avoided. During the heat treatment or conversion of the carbon compounds, a carbon-containing coating is preferably produced which comprises or consists of structured carbon. The decomposition is carried out in particular with the exclusion of atmospheric oxygen and preferably with the exclusion of other oxidizing gases or liquids.

[0103] The term "coating" or "carbon-containing coating" means that silicon is at least partially, and in particular substantially completely, surrounded or covered by a carbon-containing product of a heat-treated carbon compound. This includes thin coatings and carbon matrices in which the silicon is embedded.

[0104] The specific surface area of ​​the composite material can be adjusted in a targeted manner by appropriate selection of the temperature in step B. A lower temperature leads to a higher specific surface area, a higher temperature leads to a smaller specific surface area.

[0105] [Crush] In one embodiment, the silicon is milled before the heat treatment, in particular before step A. The milling can include breaking, grinding, deagglomeration, rolling, shredding, fragmentation and / or milling. The milling can be carried out in a low-oxygen atmosphere as described above and / or in a suitable process liquid (e.g., dispersant). In one preferred embodiment, paraffin is used as dispersant. Paraffin ensures, during the milling of the silicon, the exclusion of air from the Si surface newly created during milling. In another preferred embodiment, paraffin serves simultaneously as dispersant and carbon source. The silicon is milled in particular to a particle size D90 of less than 500 nm or less than 300 nm. In one embodiment, the particle size D90 is at least 50 nm. The particle size can be measured by dynamic light scattering or by REM. Since new silicon surfaces are created by milling, it is advantageous to mill the silicon before the heat treatment, in particular immediately before the heat treatment. These surfaces are not initially covered with an oxide layer, and it is expected that the immediately formed native oxide layer is relatively thin or is still substantially absent as a result of milling, which can be advantageous. Silicon dioxide forms silicates, which together with lithium increase the internal resistance of the battery during charging. The active materials (silicon and lithium) form SiO x Continue stirring until the SiO layer is completely converted. x The lithium is converted by reaction with lithium. In this case, lithium is lost to the charge carrier transport of the battery, increasing the internal resistance of the battery. However, this is undesirable and is preferably minimized.

[0106] Alternatively, or in addition to the grinding step of silicon before step A, the first heat-treated intermediate product is optionally ground, in particular milled. In particular, a free-flowing intermediate product is obtained, which can be effectively further processed. A further advantage is that the further grinding of the silicon carbon composite after step B is significantly easier if the heat-treated intermediate product is already ground. Advantageously, the heat-treated intermediate product is ground to a particle size D90 of less than 50 μm or less than 35 μm. The D10 value of the particle size relative to the mass distribution of the particles may be greater than 500 nm.

[0107] In one preferred embodiment, graphite can be added to the heat treated intermediate product before or after the grinding step to obtain the blend. The blend can then be subjected to a heat treatment step according to step B. The graphite proportion is preferably selected so as to maintain the desired carbon proportion in the composite material.

[0108] In one embodiment, the silicon-carbon composite is ground after step B, in particular to a particle size D90 of more than 1 μm or in the range of more than 1 μm to 35 μm, with the exception that the particle size distribution is targeted or set to have a D50 value greater than the D50 value of the particle size distribution of the silicon particles before the heat treatment with the carbon compound. The grinding is favorable to obtain a composite material in particulate form that can be further effectively processed to form a paste or slurry. Such a slurry or paste, with the appropriate selection of binders and additives, serves to spread the Si / C composite on a metal foil, preferably a Cu foil, to generate an anode surface. The grinding can preferably also be limited to the destruction of smaller Si / C composite aggregates, especially when the heat-treated intermediate product is ground, especially when a hydrocarbon, such as paraffin, is used as the carbon source. It has been shown that fewer solid sintered bodies are formed in step B when the intermediate product is already ground, especially when paraffin is used as the carbon source. As a result of this, the energy requirements of the method are significantly lower overall. Furthermore, the generation of new uncoated silicon surfaces during grinding after temperature treatment is minimized or prevented.

[0109] In one embodiment, the composite material is sieved to largely or completely eliminate particle sizes, particularly below 500 nm and above 35 μm. The composite material preferably has, with respect to its mass-related particle size distribution, a D10 value above 500 nm and / or a D90 value below 35 μm.

[0110] [Composite materials] Silicon-carbon composite materials are also according to the invention, and in particular can be obtained according to the method described herein. The composite materials, when used in batteries, are characterized by particularly low coulombic losses. In particular, the materials in half-cell tests have an average coulombic efficiency of at least 99.5% over 1000 charge / discharge cycles, especially for charge capacities of at least 1000 mAh per gram of silicon, and in particular 1200 mAh per gram of silicon or more. The composite materials can have a specific discharge capacity of at least 1000 mAh / g silicon or at least 1200 mAh / g silicon over more than 1000 charge / discharge cycles in half-cell tests.

[0111] The composite material may have a silicon proportion of at least 20% by weight, at least more than 40% by weight, at least 51% by weight, in particular at least 60% by weight, at least 70% by weight or at least 80% by weight, more preferably at least 90% by weight and most preferably at least 95% by weight, relative to the total mass of the material, in one embodiment the proportion is up to 99% by weight or up to 95% by weight.

[0112] The composite material may have a carbon percentage of 1 to 60% by weight, in particular at least 5% by weight or at least 9% by weight, relative to the total mass of the material. In certain embodiments, the composite material may also have a carbon percentage of less than 1% by weight, relative to the total mass of the material. A sufficiently high carbon percentage reduces the coulombic losses of battery cells made with the composite material. The initial capacity is indeed lower at a correspondingly higher silicon percentage in the case of a high carbon percentage, compared to a lower percentage. However, the capacity stabilizes quickly and at a surprisingly high level after the initial drop. Nevertheless, the carbon percentage should be limited upwards, in particular to a maximum of 55% by weight, a maximum of 50% by weight or a maximum of 25% by weight. The carbon percentage may contain a certain percentage of graphite in addition to the carbon derived from the carbon compound.

[0113] In one preferred embodiment, the silicon and carbon content of the composite material can be adjusted for the anode side so that the charge capacity and cycle stability are balanced with those of the cathode side of the battery. In this case, the composite material resulting from the heat treatment is considered to be mixed as a "drop-in replacement" with graphite materials known from the prior art as a blend that produces the desired balanced (anode and cathode side) battery capacity.

[0114] The material is preferably in the form of a composite material, in particular having a particle size D90 of less than 50 μm, less than 20 μm or less than 10 μm. In one embodiment, the particle size D90 is greater than 1 μm. In one embodiment, the composite material is substantially free of particles smaller than 500 nm. In particular, the D10 value is greater than 500 nm for the mass distribution of particles.

[0115] The composite material optionally has substantially no particles larger than 35 μm, or larger than 25 μm, or larger than 20 μm, or larger than 10 μm. Particles smaller than 500 nm and / or larger than 35 μm can optionally be largely removed by filtration.

[0116] In one embodiment, at least a plurality, particularly most or all of the composite particles, comprise at least two silicon particles per composite particle. The silicon particles have a particle size D90 of less than 300 nm or less than 200 nm. The measurement of particle size in the composite material can be carried out by REM. If not specified, Martin diameter is meant.

[0117] The specific surface area of ​​the composite particles is 300m 2 / g, especially 40~300m 2 In particular, the specific surface area can be in the range of 10 to 100 m 2 / g. The specific surface area can be measured by the BET method (e.g. according to DIN ISO 9277:2014). It has been shown that it is advantageous to set the specific surface area smaller, which can result in a reduction in parasitic reactions.

[0118] [Use and battery cells] The use of the composite material described herein, optionally with further additives such as graphite, as an anode material in a battery cell is also according to the invention. In the anode material, the mass ratio of carbon to silicon can be at most 1:1, preferably at most 4:10, in particular at most 2:10 or at most 1.5:10. The anode material contains the composite material according to the invention. As a result of the high proportion of silicon, the maximum charge of the correspondingly equipped battery can be significantly increased. This mass ratio is preferably already adjusted in the method according to the invention by the selection of the amount of silicon and carbon compound. A lithium-ion battery cell containing the anode material is also according to the invention.

[0119] Also according to the invention is a battery cell comprising an anode at least partially composed of the composite material described herein. The anode is optionally composed of at least 10% by weight, in particular at least 20% by weight or at least 60% by weight of the composite material. In addition to the composite material, the anode can optionally contain further carbon, for example in the form of graphite and / or carbon black and / or binder.

[0120] The battery further preferably comprises a battery housing, a cathode, a separator and an electrolyte. Among others, a standard electrolyte such as LP30, in which the conductive salt LiPF6 is dissolved in a 1M solution of ethylene carbonate and dimethyl carbonate (EC:DMC=1:1), is considered. The electrolyte added to the battery cell / half cell may contain additives, in particular in an overall proportion of up to 15% by weight or up to 12% by weight relative to the mass of the electrolyte. In particular, the electrolyte (e.g. LP30) may contain up to 10% by weight of FEC (fluoroethylene carbonate) and / or up to 2% by weight of VC (vinylene carbonate) relative to the mass of the electrolyte. The additives may be selected from FEC (fluoroethylene carbonate), VC (vinyl carbonate), LiBOB (lithium-bis(oxalato)borate) and combinations thereof. These additives may improve the conductivity of the interphase (SEI) between the active material and the electrolyte. However, these additives may cause the formation of gas at higher temperatures (e.g., 50-60°C). One advantage of the present invention is that the additives in the battery cell having the composite material can be used in reduced amounts, in particular in amounts less than 10 wt.%, or less than 3.0 wt.%, or less than 0.5 wt.%, relative to the mass of the electrolyte. The proportion of the additives can optionally be at least 0.1 wt.% or at least 1 wt.%. In one preferred embodiment, the present invention includes a battery cell that is substantially free of the aforementioned additives.

[0121] The process steps for producing a carbon coated silicon anode are given below. The M1:Si powder is mixed with a solution of, for example, ethylene glycol and saccharose as carbon compounds. Alternatively, the ethylene glycol as dispersant can be replaced by a hydrocarbon, for example paraffin. In this context, it is also possible to use paraffin as the carbon source and to largely or completely omit saccharose or other carbohydrates. Process T1 (Step A): The dispersion is heated to about 180°C and the temperature is maintained until the solvent evaporates, the sugar caramelizes and the structure is formed. This process is realized in a nitrogen and / or protective gas atmosphere (the protective gas can be optionally omitted). When using paraffin as carbon source and / or dispersant, the dispersion is heated to a temperature ranging from 120°C to 700°C, preferably from 150°C to 600°C. Z1: After process T1, the intermediate product is optionally ground. In this case, a well-defined particle size distribution can be targeted. The goal is in particular to achieve a particle size close to that of the desired final product, ideally so that after T2 further grinding steps are no longer required (at most to break up looser agglomerates). When using paraffin as carbon source and / or dispersant, potentially occurring large agglomerates can also be easily broken down again after the subsequent steps of the method according to the invention, so that the final particle size can be achieved even without intermediate grinding. M2: The product can be optionally mixed with graphite at this point to complete the subsequent thermal process together to form a blended material. Process T2 (Step B): If the material is thermally threatened by higher temperatures, change to another process equipment. The temperature is increased from 750°C to 2600°C, preferably maintained at 750°C to 1100°C, in a nitrogen and / or argon and / or protective gas atmosphere and / or reducing atmosphere, until the transformation of the carbon compounds to structured carbon is completed to the desired extent. A composite material of silicon particles embedded in a carbon matrix is ​​produced. The material is cooled to room temperature in a N2 atmosphere, alternatively, preferably in an Ar atmosphere or in vacuum. Z3: The material may optionally be ground and / or sieved. EXAMPLES

[0122] [Manufacturing of silicon-carbon composite materials] The method according to the invention can be implemented in various configurations. In particular, it can be used with or without a dispersant. The mass ratio of silicon to carbon can be varied. The invention is not limited to the following examples.

[0123] Example I Silicone and sucrose were mixed together in a dispersant. Ethylene glycol was used as the dispersant. Sucrose served as the carbon compound. The mass ratio in the mixture (silicon:sucrose:dispersant) was about 2:10:15.

[0124] The mixture was transferred to a crucible for heat treatment, which had a capacity exceeding the volume of the mixture to prevent the mixture from spilling out due to foaming.

[0125] The crucibles were transferred into a push-through furnace for the first heat treatment (step A), where they were treated at 180°C for 15 hours. The transition temperature of sucrose is 160°C. The heat treatment was carried out in a nitrogen atmosphere. During the heat treatment, the sucrose lost about 15% of its mass and was caramelized.

[0126] The product of the first heat treatment (heat treated intermediate product) was subsequently 3 The material was ground in such a manner as to obtain an average bulk material density of

[0127] The ground intermediate product was subsequently transferred to a rotary kiln where it underwent a second heat treatment at 1600 °C for 6 h (step B). The heat treatment was carried out in a nitrogen atmosphere. The mass loss was about 60%. The resulting silicon-carbon composite was then milled using a multi-stage roller mill to a particle size D90 in the range of 10-20 μm. The composite had a silicon percentage of 50 wt.% and a carbon percentage of 50 wt.%.

[0128] Example II Silicone and sucrose were mixed together without any dispersing agent. Sucrose served as the carbon compound. The mass ratio in the mixture (silicon:sucrose) was about 9:5.

[0129] The mixture was transferred to a crucible for heat treatment, which had a capacity equivalent to the volume of the mixture, since there was no risk of the mixture spilling out due to the absence of a dispersing agent.

[0130] The crucible was transferred into a push-through furnace for the first heat treatment (step A), where it was treated at 180° C. for 1 h. The heat treatment was carried out in an air atmosphere. During the heat treatment, the sucrose lost about 15% of its mass and was caramelized.

[0131] The product of the first heat treatment (heat treated intermediate product) was subsequently 3 The material was ground in such a manner as to obtain an average bulk material density of

[0132] The ground intermediate product was subsequently transferred to a rotary kiln where it underwent a second heat treatment at 1400 °C for 1 h (step B). The heat treatment was carried out in a nitrogen atmosphere. The mass loss was about 25%. The resulting silicon-carbon composite was then milled using a multi-stage roller mill to a particle size D90 in the range of 10-35 μm. The composite had a silicon percentage of 90 wt.% and a carbon percentage of 10 wt.%.

[0133] Example III Silicon with an average particle size of 100 nm, graphene oxide and sucrose were mixed together in isopropanol as a dispersant. Sucrose served as the carbon compound. The mass ratio in the mixture (silicon:sucrose:graphene oxide:isopropanol) was approximately 20:100:1:850.

[0134] The mixture was first milled together in a ball mill, after which the dispersant was completely evaporated at 80° C. in an air atmosphere and the remaining mixture was transferred to a crucible.

[0135] The crucibles were transferred into a synthesis furnace for the first heat treatment (step A), where they were treated at 180° C. for 15 hours. The heat treatment was carried out in a nitrogen atmosphere.

[0136] The intermediate product was then subjected to a second heat treatment at 1280°C for 6 hours (step B). The heat treatment was carried out in a nitrogen atmosphere. The silicon-carbon composite material was then milled in a mortar. The composite material had a silicon content of 50% by weight and a carbon content of 50% by weight.

[0137] Example IV Silicon (31.01 wt%), graphene oxide (0.09 wt%) and sucrose (17.23 wt%) were mixed together in a dispersing agent (51.67 wt%). Ethylene glycol was used as the dispersing agent. Sucrose served as the carbon compound.

[0138] The mixture was transferred into a chamber furnace for the first heat treatment (Step A), where it was treated at 180° C. for 15 hours. The heat treatment was carried out in a nitrogen atmosphere.

[0139] This was followed by a second heat treatment at 1100° C. for 6 hours (Step B). The heat treatment was carried out in a nitrogen atmosphere.

[0140] Example V Any amount of silicon powder with a particle size of D90=150 μm, which also has a native oxide layer on its surface, is mixed with a sufficient amount of ethylene glycol so that the powder is completely covered by the liquid. The ethylene glycol should prevent the silicon from coming into contact with oxygen during the subsequent milling.

[0141] The corresponding amount of sucrose was added to the above mixture and stirred until the sugar was dissolved in ethylene glycol. The calculated or experimentally obtained yield from the thermal conversion of sucrose to structured carbon at a temperature of 850° C. is about 20% relative to the mass of sucrose used. The mixture is therefore selected to give a silicon to structured carbon ratio of 9:1.

[0142] The mixture is transferred to a zirconium oxide milling cup with 3 mm diameter zirconium oxide milling balls until the milling balls are just covered by the mixture. The milling cup is then closed and inserted into a planetary ball mill and milled at a speed of 500 rpm.

[0143] The resulting dispersion is loaded into a ceramic crucible and placed in a synthesis furnace, followed by a thermal synthesis process in a protective nitrogen atmosphere in the following sub-steps: a. The temperature is increased to 180°C and maintained at this temperature for 15 hours in order to evaporate the ethylene glycol and caramelize the sucrose. b. The temperature is increased to 850° C. and maintained at this temperature for 6 hours in order to pyrolyze the carbon source as completely as possible and to generate a multilayer of structured carbon around the silicon particles. c. Cool to room temperature in a protective atmosphere.

[0144] The synthesis product is ground in a mortar to break down agglomerates and processed into a compressible paste on a three-roll mill with the addition of carbon black, binder and deionized water.

[0145] The paste is spread with a blade to form a layer on the copper foil and then dried.

[0146] Elements are stamped or cut from the coated copper foil and further processed to form battery cells (see Half-Cell Testing below for more details).

[0147] The Raman spectrum of the product of this method was recorded and is shown in Figure 1. Shown are the overlaid Raman spectra of the produced material, as well as, for comparison purposes, the spectra of pure silicon and pure graphene nanosheets (GNS). It is clear that the material synthesized here has all the characteristics of silicon and GNS (see also S. Stankovich et al., Carbon 45 (2007) 1558-1565). It is clear that the produced material contains silicon coated with several incoherent graphene layers. Figure 2 shows the XRD spectrum of GNS.

[0148] [Evaluation of results] Test cells were made with the composite material according to the invention. The amount of charge flowing during charging and discharging was measured by repeatedly charging and discharging the battery test cell. Particular attention is paid here to the extent to which the specific level of charge that can be removed at most during discharge is reduced (degradation of the battery) and how high the ratio between the charge supplied during charging and the charge removed during the subsequent discharge is. From this, it is possible to determine to what extent undesirable secondary reactions occur. This value is particularly important in the first cycle, since an unavoidable side reaction occurs (the formation of a passivation layer on the negative electrode). By using the method according to the invention, it was possible to significantly reduce the extent of these secondary reactions. Figure 3 shows how the method according to the invention can be used to significantly limit the extent of secondary reactions, based on two different variants of a test cell with a Si / C composite anode. Variation 2 (Figure 3B) shows in this case a significantly reduced charge loss than in the case of variant 1 (Figure 3A), and therefore also a lower extent of secondary reactions. This was achieved by improved process control. It was also possible to significantly reduce the degradation of the material for a specific available storage capacity by using this method. The difference in degradation characteristics of battery cells with silicon anodes using unprotected silicon (with and without electrolyte additive) compared to carbon-coated silicon is shown in Figure 4. It can be seen that the usable capacity of the unprotected silicon cell decreases significantly over charge / discharge cycles, whereas the carbon-protected variant only decreases slightly over cycles.

[0149] [Half-cell test] To test the cycling stability, a half-cell in the form of a button battery was fabricated using the silicon-carbon composite in a Si / C-based electrode. A half-cell is a test cell where the Si / C-based electrode is tested against lithium as a counter electrode. The function of the Si / C composite as an electrode material is tested in a targeted manner using this test.

[0150] To obtain a Si / C electrode from the composite, the ground Si / C composite (e.g., D90<35 μm) was added to a water-soluble sodium alginate binder together with carbon black and mixed uniformly in a speed mixer at up to 3000 rpm. The alginate binder was prepared according to the formula of Liu et al. (Liu, Jingquan et al. "High-performance alginate hydrogel binder for Si / C anodes in Li-ion batteries" Chemical communications 50 48 (2014): 6386-9). Deionized water: sodium alginate: CaCl2 was added in a mass ratio of 100: 3: 0.03 and evaporated with continuous stirring at about 80 °C to a residual solid content of about 10 wt% water.

[0151] 65% Si / C composite with 25% alginate binder solids and 10% carbon black were mixed in a speed mixer in proportion to the pure solids of the alginate binder. The water content of the binder can also be adapted, if necessary, to affect the rheology of the resulting paste / slurry.

[0152] After mixing the components, the resulting paste is homogenized in a three-roll mill to break down particle agglomerates. The initial gap of the three-roll mill is preferably set to, for example, 20 μm in order to obtain a layer coating weight (wet coating thickness) of about 30 μm during printing.

[0153] The resulting paste is printed onto a thin Cu foil after a rolling process and then dried. The environmentally friendly solvent (moisture) is largely removed from the printed layer so that the binder can effectively bond and crosslink with the surface of the Cu foil. The print is dried by excluding air so that the moisture is virtually completely removed from the print.

[0154] Circular coins with defined diameters (e.g., 14 mm, 16 mm, or 18 mm) are punched out from the Cu foils printed with the Si / C composites, the percentage of Si / C active material in these coins is weighed, and the percentages of each Si and C in the active material are calculated from the synthesis conditions.

[0155] The theoretical specific maximum capacity per gram of active material (Si / C composite) can be calculated from this.

[0156] The button cell (half cell) is then assembled in an inert atmosphere (e.g. argon) with the exclusion of air. The coin made of the composite material is placed centrally on the Cu foil with the Cu side in the first housing half of the button cell. In this case, the housing has a larger diameter than the punched coin.

[0157] A separator (e.g. a Whatman glass fiber separator with a thickness of 1 mm) is inserted concentrically over the composite material in the first housing half as well. The diameter of the separator is usually just as large as or larger than the diameter of the coin with the Si / C material, but also smaller than the inner diameter of the battery housing of the button cell. The electrolyte mixture (see below) is dripped / soaked into this separator. Usually about 100-200 μL is enough for this.

[0158] A Li counter electrode of sufficient thickness is inserted concentrically over the thus-dropped electrolyte in a half-cell configuration. The thickness of the counter electrode is chosen so that the availability of Li does not limit the performance of the half-cell. The diameter of the Li coin again tends to be smaller than, or at most the same size as, the separator diameter.

[0159] A spacer with appropriate thickness and spring is placed on the Li counter electrode. The second housing half is then placed concentrically and then pressed onto the housing cover with a pressure of 6 tons, and the housing is then tightly sealed.

[0160] A standard electrolyte (brand name LP30) was used containing, in addition to the conductive salt (LiPF6), ethylene carbonate EC: dimethyl carbonate DMC (ratio 1:1) and two additives, fluoroethylene carbonate FEC (10 wt%) and vinylene carbonate VC (2 wt%).

[0161] The half-cells were then subjected to what is known as a forming process, in which the target charge / discharge conditions were first implemented at low charge rates before cycling tests were carried out. The forming was carried out at about 1 / 30C (twice) using the CC method with a voltage limit of 100mV in each case.

[0162] Immediately afterwards, for testing purposes, 1300 cycles were carried out at room temperature (20 °C) at 1C using the CC / CV method with a voltage limit of 100 mV / 1.5 V. CC denotes a charging process at "constant current" (fixed current value) up to a defined final voltage. CV denotes "constant voltage" (fixed charging voltage). The C-rate (C / 30 or 1C) indicates the time over which the battery capacity is charged. 1C corresponds to a charging process of the full capacity within 1 hour. C / 30 means that the charging process lasts 30 hours. In the case of the aforementioned voltage limit of 1.5 V, in each case only a part of the maximum available capacity of the Si / C-based electrode is charged and / or discharged again.

[0163] Half-cell testing limited the specific charge capacity to 1200 mAh per gram of silicon.

[0164] A battery cell tester from manufacturer Neware was used for the half-cell testing.

[0165] [Discharge capacity] Figure 5 illustrates the performance of the composite material according to the invention by plotting the discharge capacity in the half-cell test described above as a function of cycle number while limiting the specific charge capacity to 1200 mAh / g, thus demonstrating that the starting value of the specific discharge capacity can be maintained even for well over 1000 cycles.

[0166] [EDX-REM analysis] Figure 6A shows an REM image of a silicon-carbon composite obtained according to the present invention. A mass ratio of silicon and paraffin of 1:4.3 was used in the synthesis of this composite. The REM image was recorded at 5.0 kV, 15,050x magnification, and a working distance of 4.8 mm.

[0167] Figure 6B shows an EDX image. The composition of the silicon carbon composite was determined using energy dispersive X-ray spectroscopy (English abbreviation EDX; Quantax, Bruker Nano GmbH) at four measurement points close to the surface at 7.0 kV, magnification 10,000 and working distance 4.5 mm. The carbon fraction varies over a wider range, showing a dependence on the choice of measurement point, i.e. on the orientation of the particle surface. The detected oxygen is presumably due to the native oxide layer on the silicon particles.

[0168] [Table 13]

[0169] [Thermogravimetric analysis (TGA)] Thermogravimetric measurements with downstream mass analysis of evolved or escaping reaction gases were carried out. As an example, two measurement results according to the invention are reproduced here. In both cases, a nitrogen atmosphere with a relatively low volumetric flow rate was used during the thermogravimetric analysis (TGA). Additional tests on pure silicon wafers in the same atmosphere (without further additives) allowed to demonstrate the presence of small residual amounts of oxygen in the measurement device. This was the result of the presence of very small leak paths in the seals of the measurement chamber at high temperatures or introduced by the nitrogen flushing gas itself. Silicon wafers (in nitrogen atmosphere) showed an increased silicon oxide layer on their surface following the same temperature-time profile as that used for the TGA. However, such tests are favored in an almost pure nitrogen atmosphere.

[0170] The temperature-time profile for the TGA was adapted to the measurement process and its limitations and is represented in FIG. 8A.

[0171] In the first example, the synthesis of silicon nanopowder, saccharose and a simple dihydric alcohol as a dispersant was carried out. The mass ratio of the starting materials was selected as Si: saccharose: dispersant = 1: 0.556: 1.666. The total mass was selected to be relatively small so that the leaking gas could be transported quickly in the industrial implementation of this method.

[0172] The associated TGA profile shows the change in mass in percent starting from 100% starting synthesis mass as a function of the temperature reached for the temperature-time profile used (FIG. 8B). From this it is clear that the various conversion processes usually carried out in the first temperature treatment step A according to the invention are carried out up to a temperature slightly above 300 ° C. Further transitions in the usually separate second temperature transition step B no longer result in abrupt changes in mass. Nevertheless, further conversion of the synthesis products takes place here. The process gases escaping in this case separate or escape from the synthesis volume, initially resulting in a continuous further decrease in the mass of the synthesis volume. The slight increase in synthesis mass above about 900 ° C can be caused by the fact that the residual oxygen atmosphere reacts with the Si particles or the carbon source. As it was possible to show by separate evidence of TGA with pure silicon wafers in a nitrogen atmosphere, the formation of a thin silicon oxide layer on the silicon surface can occur unless the residual oxygen can be completely excluded from the system.

[0173] In addition to the TGA, a mass analysis of the exhaust gases escaping from the measurement chamber together with the supplied nitrogen was performed (Figure 8C). It is pointed out that a relatively low nitrogen flushing gas throughflow rate was chosen. The mass analysis was performed qualitatively and an absolute scaling of the respective fugitive substances was omitted. The mapping was further limited to a few key compounds or fugitive gases that were analyzed as significant and relevant in the mass spectrometer. Regarding the temperature-time profile for the TGA (Figure 8A) and the associated mass analysis of the outgoing air stream, it is clear that water vapor, methane, hydrogen and CO2 as well as OH groups, methyl groups are still separated or partitioned to a significant extent from the synthesis volume at temperatures significantly above 300 °C (time profile >> 200 min) (Figure 8C).

[0174] In a second example, a synthesis is carried out with two starting materials, namely silicon nanoparticles (Si) and white oil (paraffin), where the white oil simultaneously acts as dispersant and carbon source. The synthesis composition was carried out in a mass ratio Si:paraffin = 1:5 (Figure 8D). In contrast to the first example, the first transformation of the synthesis composition is carried out only at temperatures higher than 200 ° C, then first continuously up to a temperature of about 350 ° C, which is why a maximum temperature of the first temperature treatment step A is chosen that is slightly higher than this temperature. However, it is clear to the skilled person that a synthesis is also possible in which the first transformation can be replaced by a higher (up to 700 ° C) or lower temperature by appropriately selecting another hydrocarbon compound as dispersant and carbon source. When selecting another hydrocarbon compound, the maximum temperature of the first temperature treatment step A will be selected accordingly, usually in such a way that the maximum reduction in mass is already almost finished before the temperature treatment step B begins.

[0175] In contrast to the synthesis from silicon, saccharose and dihydric alcohol as dispersant, no or only very little separation of water vapor, methane, methyl groups and OH groups occurs during the synthesis of silicon with white oil (FIG. 8E). Even hydrogen escapes into the gas atmosphere only in two temperature ranges at a slightly increased rate. Only CO2 escapes back into the process atmosphere to a significant extent at temperatures significantly above 400°C. Although it is assumed that in the temperature treatment step B the process atmosphere tends to have a reducing rather than an oxidizing effect, it was observed, again in the case of TGA, that at temperatures above 900°C, low residual oxygen concentrations lead to oxidation of the as-exposed Si surface. In contrast to the measurement structure of the TGA, it is known to those skilled in the art that in a suitable manufacturing process of the synthesis it is possible to suppress the residual oxygen concentration.

[0176] [Rheology] The viscosity was measured using a rotational rheometer MCR 702 MultiDrive from Anton Paar. The measurements were performed in Twin-Drive mode, where the upper and lower plates rotate in opposite directions at the same rotation speed (50% / 50%) in order to investigate the high shear rate range. The plate-plate measurement geometry is profiled, which makes it possible to prevent or minimize sliding effects during the measurements. The profiling of the plates has a pyramidal structure (0.2 mm x 0.1 mm). The measurement parameters are as follows: plate-plate geometry with a measurement gap of 0.3 mm, room temperature of 21.5 °C, logarithmic shear rates from 0.05 to 100000 (Twin-Drive mode), logarithmic measurement point durations from 60 s to 1 s.

[0177] During the measurements, the air supply to the chamber is reduced according to the judgment of one skilled in the art to prevent rapid drying of the dispersed powder mixture. The volumetric air flow rate in the measurements shown is 0.35 m 3 h -1 Furthermore, a temperature chamber was used to protect the measurements from external influences.

[0178] Before each measurement, a waiting time (optionally 1 to 10 minutes) is observed according to the judgment of the skilled artisan, as the paste is slightly sheared by application and should reach its actual state.

Claims

1. 1. A method for producing a silicon-carbon composite material, comprising: mixing silicon particles with at least one carbon compound; heat treating the mixture in at least two steps in the following order: Including, The at least two steps include: A. heat treating the mixture at least at a temperature corresponding to the transition temperature of the carbon compound, the transition temperature of which is in the range of 150° C. to 700° C., to obtain a heat treated intermediate product; B. Heat treating the heat treated intermediate product at a temperature above 750° C. to obtain a silicon-carbon composite material; The silicon-carbon composite material has a silicon mass percent concentration of greater than 80%, and the silicon particles have a particle size D90 of less than 500 nm, the particle size D90 being at least 50 nm.

2. The method of claim 1, wherein at least one dispersant is further mixed in the mixing step.

3. The method of claim 1, wherein the transition temperature of the carbon compound is in the range of 150°C to 350°C.

4. At least step B comprises performing the step of: 2 The method according to any one of claims 1 to 3, wherein the method is carried out in an atmosphere comprising:

5. The method of claim 4, wherein step A is also carried out in a substantially oxygen-free atmosphere, in an atmosphere containing less than 100 ppmv O 2 .

6. 6. The method of claim 4 or 5, wherein the oxygen-free atmosphere is an inert gas atmosphere.

7. The method of claim 6, wherein the oxygen-free atmosphere is a nitrogen or rare gas atmosphere.

8. The method according to any one of claims 1 to 7, wherein the temperature in step A is in the range of 150°C to 600°C.

9. The method according to any one of claims 1 to 8, wherein the temperature in step B is in the range of from above 750°C to 2600°C.

10. The method according to claim 1, wherein the temperature in step B is in the range of 1000°C to 1500°C.

11. 11. The method of claim 9 or 10, wherein the temperature in step B is adjusted such that substantially no formation of silicon carbide occurs.

12. The method according to any one of claims 1 to 11, wherein the heat-treated intermediate product is ground to a particle size D90 of less than 50 μm.

13. 13. The method according to any one of claims 1 to 12, wherein the mixture of silicon and carbon compounds further comprises an additive selected from graphene, graphene oxide, graphite, fullerenes, nanotubes and combinations thereof as a structuring and / or catalytically acting additive.

14. 14. The method according to any one of claims 1 to 13, wherein the solids content in the mixture is at least 9 wt.-% and / or the silicon proportion in the silicon-carbon composite is at least 20 wt.-%.

15. The method according to any one of claims 1 to 14, wherein the minimum temperature in step B is higher than the maximum temperature in step A.

16. 16. The method of any one of claims 1 to 15, wherein the indicated temperature in step A is maintained for a period of at least 1 minute; and / or the indicated temperature in step B is maintained for a period of at least 1 minute.

17. The method according to any one of claims 1 to 16, wherein the carbon compound is a carbohydrate.

18. 18. The method according to any one of claims 1 to 17, wherein particles of the product after temperature step A or of the intermediate product between temperature steps A and B, which are smaller than 500 nm and / or larger than 35 μm, are largely removed by filtration.

19. A method according to any one of claims 1 to 18, wherein the mixture of silicon particles and at least one of the carbon compounds has a viscosity of more than 5000 mPa·s as measured by a rotational viscometer in the reverse rotation mode, a shear rate of 100 / s, and a temperature of 21.5°C.

20. 20. The method according to any one of claims 1 to 19, wherein the carbon compounds alternatively or additionally comprise at least one carbon compound selected from the list of lignin, wax, vegetable oil, fat, oil, fatty acid, gum and resin.

21. The method according to any one of claims 1 to 20, wherein the carbon compound and / or the dispersant is paraffin or paraffin oil.

22. The method of claim 1, wherein the mixture of silicon particles and at least one of the carbon compounds further comprises lithium or a lithium-containing starting material.

23. The method of claim 1, wherein the silicon is ground prior to the heat treatment and paraffin is used as a dispersant.

24. 24. The method of claim 23, wherein the silicon has a particle size D90 of less than 500 nm and / or a particle size D90 of at least 50 nm.

25. The method includes removing silicon dioxide from the surface of the silicon by etching, the etch for removing the silicon dioxide being performed using HF, KOH, NH 4 F, N.H. 4 H.F. 2 , LiPF 6 , H 3 P.O. 4 , XeF 2 , S.F. 6 The method according to any one of claims 1 to 24, which is carried out using one of the substances from the group consisting of:

26. 26. A silicon-carbon composite material obtainable according to the method of any one of claims 1 to 25, having an average coulombic efficiency over 1000 charge / discharge cycles of at least 99.5% in a half-cell test with a specific charge capacity of at least 1000 mAh / g relative to the mass of silicon in the composite, the composite material has a silicon content of 40-99% by weight and / or a carbon content of 1-60% by weight, A silicon-carbon composite material in the form of composite particles, having a particle size D90 of less than 50 μm.

27. 27. The composite material of claim 26, having a particle size D10 of more than 500 nm for the mass distribution of particles.

28. 28. The composite material of claim 26 or 27, wherein most or all of the composite particles have at least two silicon particles per composite particle.

29. Maximum 300m 2 The composite material according to any one of claims 26 to 28, having a specific surface area of ​​100 / g.

30. The composite material according to any one of claims 26 to 29, having a specific surface area in the range of 10 to 100 m 2 / g.

31. The composite material according to any one of claims 26 to 30, having a specific surface area that is no more than twice as large as the specific surface area of ​​the silicon particles in the composite material.

32. A composite material described in any one of claims 26 to 31, having a specific surface area that is less than 50% of the specific surface area of ​​the silicon particles in the composite material.

33. A composite material described in any one of claims 26 to 31, having a specific surface area smaller than the specific surface area of ​​the silicon particles in the composite material.

34. 34. The composite material of any one of claims 26 to 33, having a specific discharge capacity of at least 1000 mAh / g relative to the mass fraction of silicon in the composite material over more than 1000 charge / discharge cycles in a half-cell test.

35. Use of the composite material according to any one of claims 26 to 34 as an anode material in a battery cell.

36. A battery cell comprising an anode constructed at least in part from the composite material of any one of claims 26 to 34.

Citation Information

Patent Citations

  • Si / C COMPOSITES AS ANODE MATERIALS FOR LITHIUM ION BATTERIES

    JP2014183043A

  • Si / C COMPOSITES AS ANODE MATERIALS FOR LITHIUM ION BATTERIES

    US20140287315A1

  • Method for producing negative electrode material for lithium ion batteries

    US20150295233A1

  • Carbon-coated silicon particles for lithium ion batteries

    US20190305366A1

  • Electroactive materials for metal-ion batteries

    WO2016146999A1